Exploring the Core Elements of Interdisciplinary Teamwork During Surgical Procedures: A Systematic Review - Alami , Mohanna Mohammed; Alenezi , Youness Elewi J; Alharthi , Mohammed Abdulrahman; noshili, Khalid Mohammed; Alsharari, ‏ Fawaz Saud; Mojamami , Fahad Ali Jubran; al shammari, Abdullah Muhanna; Aldhafeeri, Khaled Fazzaa; Aljuhani , Mayada Abdualmunem; Alqahtani , Waleed Sayer Mobark; Ashwi, Nawal Ahmed; Aleisawi, Naif Hamaadi (Journal of Ecohumanism, 2024)
Objective: This systematic review aims to identify and analyze the core elements that underpin effective interdisciplinary teamwork in surgical environments and their influence on patient outcomes and procedural efficiency. Methods: We conducted a comprehensive search of electronic databases including PubMed, Scopus, and Web of Science for studies published between January 2000 and December 2024. The review focused on empirical research and reviews that examined teamwork dynamics in surgical settings. Inclusion criteria were studies on interdisciplinary teams involving multiple healthcare specialties in surgical procedures. Data extraction focused on teamwork components, communication patterns, and collaboration outcomes. Results: A total of 45 studies met the inclusion criteria. Analysis revealed that effective teamwork is characterized by clear communication, mutual respect, role clarity, and leadership. These elements were consistently associated with improved patient safety, reduced surgical errors, and enhanced procedural efficiency. The quality of evidence was predominantly high, indicating robust support for the critical role of interdisciplinary teamwork in surgical success. Conclusion: The core elements of interdisciplinary teamwork essential for surgical success include structured communication, well-defined roles, mutual respect among team members, and adaptive leadership. Implementing training programs that focus on these key teamwork components could significantly enhance the quality of surgical care. Future research should explore intervention studies that measure the impact of teamwork enhancement programs on surgical outcomes.